The Influence of Nutrition Education Through The Media Pocketbook on Increasing Knowledge about Healthy Snacks in State Elementary School - Arnisam; Rasmawati; Masyudi; Yuliani Safmila (Universitas Serambi Mekkah, 2024)
Research objective: to determine the effect of nutrition education through pocket books on increasing children's knowledge about healthy snacks at SD Negeri 25